Recent developments in multi-omics and breeding strategies for abiotic stress tolerance in maize (Zea mays L.) - Farooqi, Muhammad Qudrat Ullah; Nawaz, Ghazala; Wani, Shabir Hussain; Choudhary, Jeet Ram; Rana, Maneet; Sah, Rameswar Prasad; Afzal, Muhammad; Zahra, Zahra; Ganie, Showkat Ahmad; Razzaq, Ali; Reyes, Vincent Pamugas; Mahmoud, Eman A.; et al. (Frontiers in Plant Science, 2022)
High-throughput sequencing technologies (HSTs) have revolutionized crop breeding. The advent of these technologies has enabled the identification of beneficial QTL, genes, and alleles for crop improvement. Climate change has made a significant effect on the global maize yield. To date, the well-known omic approaches such as genomics, transcriptomics, proteomics, and metabolomics are being incorporated in maize breeding studies. These approaches have identified novel biological markers that are being utilized for maize improvement against various abiotic stresses. This review discusses the current information on the morpho-physiological and molecular mechanism of abiotic stress tolerance in maize. The utilization of omics approaches to improve abiotic stress tolerance in maize is highlighted. As compared to single approach, the integration of multi-omics offers a great potential in addressing the challenges of abiotic stresses of maize productivity.